PISANG GEN ALFA: Smartphone Application for Mental Health Families of Alpha Generation in Indonesia - Alfianto, Ahmad Guntur; Ekaprasetia, Feri (Journal of A Sustainable Global South, 2023)
Families with alpha generation in the industrial era 4.0 have problems in mental health care, however, effortare made to prevent the occurrence through health education. The prevention model in the industrial revolution era 4.0 used a mobile application on a smart phone. PISANG GEN ALFA is a smartphone application that contains the method of parenting, assertive care, and stress management. The purpose of this study is to develop PISANG GEN ALFA as an application for reducing mental health problems in families with alpha generation. The application was developed through two stages, the first was carried out by creating application content and sophisticated systems by technology experts. Furthermore, in the second stage, a perception test was performed in the fields of mental, pediatric, and maternity nursing. Then, 100 families with alpha generation children were assessed in Malang Regency, East Java, Indonesia using a learning media questionnaire, and Intraclass Correlation Coefficients (ICC) test. The application consists of Education menu about PISANG GEN ALFA, parenting in industrial revolution era 4.0, stress prevention and management, assertive care, and parenting tension. The statistical analysis showed the value of 0.875, while the average of 3 assessors was 0.964> 0.5 (high stability). Furthermore, from the diligence results, 86.78% of the families stated that the application was very suitable for use, while 13.22% commented that it was feasible. PISANG GEN ALFA was a health education application used for families with alpha generation children in reducing mental health problems during parenting.